PENGARUH DISIPLIN DAN LAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN MUARA KULAM KECAMATAN ULU RAWAS KABUPATEN MUSI RAWAS UTARA - Siti Zahro; Mulyadi Mulyadi (Jurnal Interprof, 2019)
The objectives of this research are: 1) To know the influence of discipline and public service to the satisfaction of society in Muara Kulam village, Ulu Rawas District, North Musi Rawas Regency. 2) To know the influence of discipline to the satisfaction of society in Muara Kulam Subdistrict, Ulu Rawas District, North Musi Rawas Regency. 3) To know The influence of public service to the satisfaction of the community in the Village Office of Muara KulamSubdistrict, Ulu Rawas District, North Musi Rawas Regency. The result of t test above can be explained as follows: that the discipline variable (X1) to the satisfaction of the community in the Village Office of Muara Kulam SubdistrictUlu Rawas North Musi Rawas Regency shows that the value of t = 3.855 is bigger than the value of ttable 2.021 with significant level = 0,000 < (α) 0.05, df (n-2) 50 - 2 = 48 is 2.021, this shows Ho is rejected and Ha accepted and partially variable discipline has a significant influence on the satisfaction of society in Muara Kulam Subdistrict Ulu Rawas District Musi Rawas Regency North. (X2) The influence of public service to the satisfaction of the community in the Village Office of Muara Kulam Subdistrict, Ulu Rawas District, North Musi Rawas Regency. Showing thitung = 4,601 is bigger than ttable value 2.021 with significant level = 0,000 <(α) 0.05, df (n-2) 50 - 2 = 48 is 2.021, it shows Ho rejected and Ha accepted and partially service variable public has a significant influence on community satisfaction in the Village Muara Kulam Ulu RawasDistrict North Musi Rawas District. The result of Fcount obtained is 15.780> Ftable = 3.20 and significance level simultaneously significance is 0,000 <(α) = 0,05 df = n - k = 50 - 2 - 1 = 47 is 3.20 so Ho is rejected and Ha accepted. means that simultaneously the independent variables X1 (discipline) and X2 (public service) have a significant influence on the dependent variable Y (community satisfaction) so proved true and hypothesis is acceptable.